2(6x-3)=8x+2

Simple and best practice solution for 2(6x-3)=8x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6x-3)=8x+2 equation:


Simplifying
2(6x + -3) = 8x + 2

Reorder the terms:
2(-3 + 6x) = 8x + 2
(-3 * 2 + 6x * 2) = 8x + 2
(-6 + 12x) = 8x + 2

Reorder the terms:
-6 + 12x = 2 + 8x

Solving
-6 + 12x = 2 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-6 + 12x + -8x = 2 + 8x + -8x

Combine like terms: 12x + -8x = 4x
-6 + 4x = 2 + 8x + -8x

Combine like terms: 8x + -8x = 0
-6 + 4x = 2 + 0
-6 + 4x = 2

Add '6' to each side of the equation.
-6 + 6 + 4x = 2 + 6

Combine like terms: -6 + 6 = 0
0 + 4x = 2 + 6
4x = 2 + 6

Combine like terms: 2 + 6 = 8
4x = 8

Divide each side by '4'.
x = 2

Simplifying
x = 2

See similar equations:

| 4x(2x^3-4x^2-x)= | | 4u+5u=27 | | -7x+37=-7+2(1-7x) | | 12u-5u=42 | | 2(x-2)-(3x-7)=3(4x-1)-7 | | -7(2-3k)=3k+40 | | 8x^4-16x^3-4x^2= | | 3y+11x= | | -9(t-2)-2(t+1)=-10 | | n^2-13n-50=0 | | 5x-(2x+3)=x-6 | | -97=-6(x+8)-7 | | 2k^2+9k=7 | | 5r^2-36r-32=0 | | 253=-2-5(7k+5) | | n^2-13n+50=0 | | -z+4=26 | | -3(8y-5)=4(1-7y)+14 | | Vf=0+0*20 | | 100x+90-x=99 | | 1+3n=1+3n | | 12+2[6+7(x+1)]=0 | | (X+21)+(x+61)+(X+23)=180 | | 1/4x^4-4 | | x-6=4x-2x-9 | | -21x+18x=3(-6-2x) | | 2.9x+4.5x= | | 2b(2a-x)=x(b-a)+a(x+b) | | X^2/3=10 | | 5(x-7)+6=5x-23 | | (2x+3)*(4x+7)=8x^2-5 | | X+(X+55)+(X+38)=180 |

Equations solver categories